PERANAN ALAT BANTU PENGIRIMAN ARSIP AEROCOM PNEUMATIC TUBE SYSTEM PADA PEMERIKSAAN VERTEBRAE CERVICAL DENGAN KASUS TRAUMA - Ryzki Mega Mentari; Nanang Sulaksono (Perhimpunan Radiografer Indonesia (PARI), 2018)
Background :The cervical vertebrae consist of seven vertebral bones separated by intervertebral discs and connected by complex ligamentous tissue. Examination of cervical vertebrae includes Axial, Lateral, RPO and LPO AP projections. Axial AP projections are carried out with15-200 cephalad angles. At PKU Muhammadiyah Hospital Gamping vertebrae radiographic examination cervical AP projection was done without cornering this case there was a difference with the theory so the author wanted to know more about the examination procedure. Methods :This type of research is qualitative research with a case study approach. This research was conducted at the Radiology Installation of PKU MuhammadiyahGamping Hospital and was carried out in March - May 2018. This research was carried out by observation, documentation, radiogarfer interviews and radiology doctors.Results :The results of the study found that cervical vertebrae radiographic examination procedures in trauma cases used two projections, namely AP and Lateral projections. On vertebrae examination cervical projection of AP is done without cornering. The reason for not being cornered is because the radiograph has revealed the corpus, intervertebral disc, spinousprocesus. Cervical vertebrae examination with trauma cases requires further action. In the Radiology Installation PKU Muhammadiyah Hospital, Gamping, was assisted by the delivery of aerocom pneumatic tube system files, in its role this tool was very helpful if the sending doctor wanted to immediately find out the radiographic results of the patient with the trauma case.